THE PROCESS OF STRUCTURING OF THE PRACTICES EVALUATIONS IN THE PHYSICAL EDUCATION: OF THE INITIAL FORMATION TO THE SCHOOL PEDAGOGIC PRACTICE (Fiep Bulletin - online, 2015)
The initial formation in physical education has been making possible the student the structuring of theoretical and practical knowledge that orientate the pedagogic practice of the professional future. In what he/she refers to the evaluation process, so much the experiences lived through the practices evaluations used by teachers that supply classes in the courses of initial formation, as well as discussions related to the theme developed in disciplines curriculars, they influence in the structuring of the pedagogic practice of futures physical education professionals. In that perspective, the objective of this investigation was to analyze the process of structuring of the practices evaluations of physical education professionals in all the teaching levels. For so much, she opted to use a descriptive-interpretative methodology with a qualitative approach of the data. The participants consisted of exits that supply classes in the public and private schools of the municipal district of Marechal Cândido Rondon - Pr, educational teachers of the career of the superior teaching that supply classes in the course, in the school period of the year of 2005, as well as the students enrolled and frequent in the 4th year of the course of physical education of Unioeste. The instrument used in the collection of the data it consisted of semi-structured interview. The questions that orientated the interviews were open, to obtain varied answers on the practices evaluations. As result, identified that the professional experience was considered as the factor that more it influenced or it contributed to the structuring of the practices evaluations, so much of the teachers college as of the teachers exits.
Keywords: .